An Inducible Human Immunodeficiency Virus Type 1 (HIV-1) Vector Which Effectively Suppresses HIV-1 Replication - An, Dong Sung (American Society for Microbiology, 1999)
Recently, gene therapy vectors based upon the human immunodeficiency virus type 1 (HIV-1) genome have been developed. Here, we create an HIV-1 vector which is defective for all HIV-1 genes, but which maintains cis-acting elements required for efficient packaging, infection, and expression. In T cells transduced by this vector, vector expression is low but efficiently induced following HIV-1 infection. Remarkably, although the HIV-1 vector does not contain specific anti-HIV-1 therapeutic genes, the presence of the vector alone is sufficient to inhibit the spread of HIV-1 infection. The mechanism of inhibition is likely to be at the level of competition for limiting substrates required for either efficient packaging or reverse transcription, thereby selecting against propagation of wild-type HIV-1. These results provide proof of a concept for potential application of a novel HIV-1 vector in HIV-1 disease.